Possibilities of Vegetation Analysis in Visible Range Drone Survey - Busznyák, János (Journal of Central European Green Innovation, 2022)
High-precision aerial surveys with Multispectral camera-equipped drones are beneficial supporting agricultural tasks. Multispectral tools are expensive, beside its widely use. In visible spectrum (Red, Green, Blue – RGB) cameras are possible cost-efficient solutions for remote sensing over vegetation areas. In this case, tasks of the preprocessing are more simply. Drone surveys were carried out over nearby winter wheat (Triticum aestivum L.) and winter coleseed (Brassica napus L.) tables three times in a row. During data processing indices of visible spectrum were compared to each other and to multispectral Normalized Differencial Vegetation Index – NDVI) data.